Synthesis of Silver Nanoparticle-Graphene Composites for Electroanalysis Applications using Chemical and Electrochemical Methods - Golinelli, Diego L.C.; Machado, Sergio A.S.; Cesarino, Ivana [UNESP] (Wiley, 2017)
An electrochemical device was developed for the simultaneous determination of sulfamethoxazole (SMX) and trimethoprim (TMP) using differential pulse voltammetry and glassy carbon (GC) electrodes modified with reduced graphene oxide (rGO) and silver nanoparticle (AgNP) composites, synthesised using both chemical and electrochemical methods. The morphology and electrochemical behaviour of the GC electrodes modified with the rGO/AgNP (chemical method) and rGO-AgNP (electrochemical method) composites were characterised by scanning electron microscopy and cyclic voltammetry. These techniques demonstrated that, in both methods, the graphene oxide was modified by the AgNPs, and the composite synthesised by the electrochemical method showed a better dispersion of the nanoparticles, resulting in an increase in the surface area compared to the rGO/AgNP composite. The GC/rGO-AgNP electrode was evaluated and optimised for the simultaneous determination of SMX and TMP, achieving detection limits of 0.6 μmol L−1 for the SMX and 0.4 μmol L−1 for the TMP. The proposed GC/rGO-AgNP electrochemical device was successfully applied to the simultaneous determination of SMX and TMP in wastewaters samples.
Keywords: Antibiotics; Graphene; Silver nanoparticles